2017
DOI: 10.5455/ijlr.20170312042556
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Post-Partum Body Condition Score on Productive, Reproductive and Calf Birth Weight Performance in Tharparkar Cattle

Abstract: The objective of study was to know the change in BCS at different stages and effect of BCS at stage II (post-partum) VIII were 4.17 ± 0.11, 4.00 ± 0.11, 3.90 ± 0.07, 3.73 ± 0.08, 3.57 ± 0.06, 3.57 ± 0.07, 3.70 ± 0.06 and 3.85 ± 0.06

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In contrast, some authors reported that pre-calving BCS was not significantly associated with reproductive performance (Buckley et al, 2003). Godara et al (2016) found that postpartum interval to estrous was significantly affected by pre-calving BCS. Chapel et al (2017) have shown that cows with BCS>3.75 had worse reproductive performance than optimal BCS (3.5-3.75).…”
Section: Discussionmentioning
confidence: 87%
“…In contrast, some authors reported that pre-calving BCS was not significantly associated with reproductive performance (Buckley et al, 2003). Godara et al (2016) found that postpartum interval to estrous was significantly affected by pre-calving BCS. Chapel et al (2017) have shown that cows with BCS>3.75 had worse reproductive performance than optimal BCS (3.5-3.75).…”
Section: Discussionmentioning
confidence: 87%